2017
DOI: 10.18632/oncotarget.18803
|View full text |Cite
|
Sign up to set email alerts
|

Target sequencing of 307 deafness genes identifies candidate genes implicated in microtia

Abstract: Microtia is a congenital malformation of the external ear caused by genetic and/or environmental factors. However, no causal genetic mutations have been identified in isolated microtia patients. In this study, we utilized targeted genomic capturing combined with next-generation sequencing to screen for mutations in 307 deafness genes in 32 microtia patients. Forty-two rare heterozygous mutations in 25 genes, including 22 novel mutations in 24 isolated unilateral microtia cases were identified. Pathway analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, GALR1 and WDR45 loci identified in the present study have been linked to congenital developmental auditory dysfunction. A large mutation screening of 307 deafness genes in patients with microtia identified GALR1 as a strong candidate gene (amongst others) with novel mutations associated with microtia (62). Microtia is a malformation of the external ear that ranges in severity from mild differences in auricular shape and size to complete absence of the external ear with atresia or stenosis of the auditory canal that may be caused by genetic and/or environmental factors (63,64).…”
Section: Tinnitusmentioning
confidence: 99%
“…Furthermore, GALR1 and WDR45 loci identified in the present study have been linked to congenital developmental auditory dysfunction. A large mutation screening of 307 deafness genes in patients with microtia identified GALR1 as a strong candidate gene (amongst others) with novel mutations associated with microtia (62). Microtia is a malformation of the external ear that ranges in severity from mild differences in auricular shape and size to complete absence of the external ear with atresia or stenosis of the auditory canal that may be caused by genetic and/or environmental factors (63,64).…”
Section: Tinnitusmentioning
confidence: 99%
“…21 Studies of congenital microtia in humans have found that the focal adhesion pathway may affect the development of ear cartilage. 22 Our results revealed gene and lncRNA expression changes involved in mouse external ear embryonic development in mice with a point mutation in the Prkra gene. In particular, changes in the lncRNA expression profile were detected during mouse embryonic auricle development from E15.5 to E17.5, suggesting that the regulation of multiple lncRNAs may contribute to the process of external ear development.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have found that the focal adhesion pathway may be closely related to the formation of microtia, which may be because the outer ear cartilage is mainly composed of elastic cartilage, which can affect the development of cartilage, resulting in external ear malformation. 20 The main limitation of this study is that functional validation was not performed following the confirmation of differential cir-cRNA expression in the development of mouse external ear embryos.…”
Section: Discussionmentioning
confidence: 99%